Investment Reversibility and Agency Cost of Debt - Manso, Gustavo (Econometrica, 2008)
Previous research has argued that debt financing affects equity-holders' investment decisions, producing substantial inefficiency. This paper shows that the size of this inefficiency depends on the degree of investment reversibility. In a dynamic model of financing and investment, the paper provides an upper bound for the inefficiency produced by debt financing. The upper bound is decreasing in the degree of investment reversibility and is zero when investment is perfectly reversible. Copyright The Econometric Society 2008.